The Effect of Human Resource Development on Job Stress with Regard to the Mediator Role of Self Concept in Shiraz University of Medical Sciences - Mehrdad Azadi; Malikeh Beheshtifar (پیاورد سلامت, 2019)
Background and Aim: Job stress is one of the reasons of low motivation and leaving onechr('39')s job, and its reduction can have positive consequences. According to studies, staffchr('39')s development and their positive self concept toward workplace can reduce job stress. The aim of this research is to study the effect of human resource development on job stress with regard to the mediator role of self concept in Shiraz University of Medical Sciences(SUMS). Materials and Methods: This is a correlational descriptive study. The research community included 584 staff members, of whom 234 were selected using Morganchr('39')s table in 2018. To collect data, 3 standard questionnaires were used, and their content validity and reliability were confirmed. For data analysis, structural equation modeling and Amos and SPSS softwares were used. Results: The findings showed that human resource development had a reverse effect on staff job stress(path coefficient -0.778). Moreover, human resource development had a direct effect on job stress(path coefficient 0.843), but staff self concept did not have any effect on job stress(path coefficient 0.166). Since the paths of human resource development-self concept and self concept-job stress were not meaningful, human resource development did not have any effect on job stress by way of the mediator variable of self concept in confidence level 0.95. Conclusion: According to the results of this study, conducting the staffchr('39')s continuous development to promote their skills and abilities for declining job stress is emphasized.